The least n for which the recursive formula is applicable is n=1, for the closed form is n=0. When we go from k to k+1 we deal with a formula
a(k+1) = a(k) + 2*a(k-1).
This recursive formula holds from k>=1, so k+1>=2 and the first n for which such a proof is possible is n=2. So we ought to check the direct form for n=1 and n=0.
The answer is 2 (base cases).
Actually, they are not true (a0 = 1 not= 2^0+(-1)^0 = 2, a1 = 3 not= 2^1+(-1)^1 = 1).
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?